Padap-sahita A book on common grasses and herbs. (International Journal of Scientific Research and Management (IJSRM), 2017)
India is a vast country with many diversities whether social diversities or biological diversities. These diversities make India a unique country in the world. I will not talk here about social diversities but I will focus on biological diversity in India. The biological diversity in India arises mainly due to different types of terrains and climatic zones. In India we can found a small runner grass to tall eucalyptus trees, from wild weeds to useful herbs. There are approx.45000and more Species of plants found in India.We can explore this diversity in our home garden even. When you will look at each plants whether weeds, herbs, shrubs etc. you will find that these plants have many uses. But unfortunately we even don’t know their name properly. So in this book I will solve these problems as in this book I am going to you about some herbs and grasses that are generally found in our homes as weeds, with full identification details and classification. So let us start exploring diversity of India from our home garden. So let us first discuss about plants. What are plants? Plants are mainly multi- cellular eukaryotic organisms of the plantae kingdom. But they can be uni- cellular like spirogyra etc. They are generally green but can be red, brown etc. In colour. Plants of the earth can be generally classified into herbs, shrubs, trees, And grasses